APPLICATION OF THE REPRESENTER METHOD FOR PARAMETER ESTIMATION IN NUMERICAL RESERVOIR MODELS - Przybysz-Jarnut Ju.K.; Hanea R.G.; Jansen Ja.; Heemink A.W. (My University, 2007)
A data assimilation method was applied to estimate poorly known parameters (permeabilities) in a numerical reservoir model. Most variational methods for data assimilation are based on the assumption that the model is perfect except for the poorly known parameters. The representer method allows also for model errors, i.e. for uncertainties in the state variables (pressures and saturations). The method is based on minimizing a cost functional, assuming all the errors and parameters to be multivariate Gaussian random variables with given mean and covariances. The uncertain parameters and variables are expanded into a finite sum of basis functions called representers, and the gradients of the cost functional are obtained with an adjoint method. This approach gives an optimal parametrization in the sense that the final result is equal to the solution of the full inverse problem. The method was tested on a simple one-dimensional model to simulate two-phase (oil-water) flow through a heterogeneous reservoir. The results show that the method is able to provide an acceptable estimate of the permeability field. We used pressure measurements from a small number of observation wells in between the injection and production wells, but the representer method could be used equally well to assimilate data from other sources. The method appears to be a promising data assimilation tool for applications in reservoir engineering.
Keywords: ADJOINT METHOD; AUTOMATIC HISTORY MATCHING; EULER-LAGRANGE EQUATIONS; ONE-DIMENSIONAL TWO-PHASE FLOW; REPRESENTER METHOD